Fracture toughness of AISI D6 tool steel as received and with heat treatment - Bressan J.D.* (2005)
AISI D6 is an alternative tool steel used as die and punch in blanking, piercing and cold forming processes. Tooling service life is limited by plastic deformations, wear and rupture due to the presence of high stresses and cracks. Present work evaluates the critical stress intensity factor K1C of AISI D6 tool steel with and without heat treatment, using the three point bending test of a notched beam or SENB specimen. Initially, a pre-crack was performed by fatigue in the notched specimen assembled in a pre-cracking mechanical equipment developed in laboratory. The fracture toughness tests were carried out in SENB specimen according to the ASTM E 399 standard. The Linear Elastic Fracture Mechanics approach was used to calculate fracture toughness of D6 tool steel heat treated and the Compliance Method of Non-linear Fracture Mechanics was utilised for calculating fracture toughness of D6 tool steel as received. The material microstructures were characterised by micrographs in an optical microscope and the ruptured surface was examined by SEM photographs. The obtained fracture toughness medium values KIC were 25.9 MPam1/2 and 44 MPam1/2 respectively for AISI D6 heat treated and as received, indicating a decrease in ductility due the heat treatment. Although, yield stress has increased 40%. The different fracture mechanisms are also shown.